EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA BOGOR NO 12 TAHUN 2009 TENTANG KAWASAN TANPA ROKOK (STUDI KASUS PELAKSANAAN KAWASAN TANPA ROKOK PADA SEKOLAH MENENGAH ATAS NEGERI DI KOTA BOGOR) - Setiawan, Nancy Purnamasari; Hernawan, Denny; Salbiah, Euis (JURNAL GOVERNANSI, 2017)
The objective of this research is to know the evaluation of Local Regulation of Bogor City Number 12 Year of 2009 about Non-Smoking Area (Case Study of the implementation of Non-Smoking Area in High School around Bogor City).The theory used in this research is policy evaluation theory proposed by William Dunn. According to Dunn to evaluate a policy there are six dimensions that can be used namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness.Method used in this research is quantitative method. Data collecting method used in this research are literature study and field study. Meanwhile, population in this study are Headmaster, Head of Administration Office, and Head of OSIS (Student Organization of Intra-School) in High School. The number of sample choosed are 30 respondents based on purposive sampling method.Based on evaluation reveals that the implementation of Local Regulation of Bogor City Number 12 Year of 2009 about Non-Smoking Area yield a score ofÂ  3,50, that means âgoodâ in criteria. Reffering to six dimensions of, effectiveness, responsiveness, and appropriateness are âgoodâ in category. On the other hand, efficiency, adequacy, and equity are dimensions with âmoderateâ in category.Â Key word : Leadership, Performance, employees